(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Structural failure and water scarcity are one of the infrastructural challenges man faces today. The importance of foundation studies before erecting civil engineering structures such as buildings and highway cannot be overemphasized. Regardless of structure put on the surface of the earth, if the foundation or the subsurface structure is weak, such structure will eventually collapse. Groundwater exploration is gaining more importance in Nigeria owning to ever increasing demand for water supplies, as rain water and surface water are either scarce to get or got polluted by human activities. The study is therefore aimed at characterizing the subsurface for engineering competence and groundwater potential in Olupona Housing Estate, Ayedire Local Government Area, Osun State, Nigeria. An integrated geophysical mapping involving the Electromagnetic (VLF-em) and Vertical Electrical Sounding (VES) were carried out around the proposed housing estate, Olupona, Southwestern Nigeria in order to evaluate subsurface competency for engineering activities and the groundwater potential beneath the study area. Seven (7) traverses were each established for VLF-em survey in S-N and E-W orientation while Sixteen (16) VES stations were deployed along five (5) traverses in order to cover the entire study area. The data obtained were analyzed and processed qualitatively and quantitatively. The VLF-em revealed several geological features which ranged from -18.0 to 12.0 Sm-1. Positive conductivity zones and negative conductivity zones were mapped in the study area. Some of the positive conductivities mapped showed that the conductive anomalies extended from surface to the depth of 40.0 m. VES analysis revealed three-to-four lithologic sequences which include topsoil, lateritic layer (not present in all), weathered layer, and fractured or fresh bedrock. H-type, HA-type and KH-type were the curve types obtained from VES data with the overburden thickness ranging from 8.0 to 51.66 m. It is concluded that the study area is underlain with thick overburden, thus making the study area unsuitable for construction of high-rise buildings. It is also affirmed that groundwater exploration is sparingly favoured in the study area.